2020
DOI: 10.1111/1365-2745.13574
|View full text |Cite
|
Sign up to set email alerts
|

Species abundance fluctuations over 31 years are associated with plant–soil feedback in a species‐rich mountain meadow

Abstract: 1. Increasing evidence suggest that plant-soil interactions play an essential role in plant community assembly processes. Empirical investigations show that plant species abundance in the field is often related to plant-soil biota interactions; however, the direction of these relations have yielded inconsistent results. 2. We combined unique 31-year long field data on species abundances from a species-rich mountain meadow with single time point plant-soil feedback greenhouse experiments of 24 co-occurring plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 83 publications
2
30
0
Order By: Relevance
“…Such sequential replacements result in high, fine‐scale dynamics in plant communities, which is line with observations in grassland communities stable in plant species numbers, that is, where plant species successfully coexist (Herben et al, 1997; Herben, Krahulec, Hadincová, & Skálová, 1993; Humphrey & Pyke, 1998; Palmer & Rusch, 2001; van der Maarel & Sykes, 1997). Moreover, our previous findings in the species‐rich mountain meadow are consistent with the proposed framework as we found that fluctuations in relative abundance of species responding negatively and positively to their own conditioned soil were coupled in time: in years that the generally higher abundant negative feedback species (superior competitors) decreased, the lower abundant positive feedback species (inferior competitors) increased, and vice versa (in ‘t Zandt et al, 2021). This balance may result from a dependency of the fast colonising, inferior competitors on the release of soil patches by slow colonising, superior competitors, akin to the proposed framework (Figure 5).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such sequential replacements result in high, fine‐scale dynamics in plant communities, which is line with observations in grassland communities stable in plant species numbers, that is, where plant species successfully coexist (Herben et al, 1997; Herben, Krahulec, Hadincová, & Skálová, 1993; Humphrey & Pyke, 1998; Palmer & Rusch, 2001; van der Maarel & Sykes, 1997). Moreover, our previous findings in the species‐rich mountain meadow are consistent with the proposed framework as we found that fluctuations in relative abundance of species responding negatively and positively to their own conditioned soil were coupled in time: in years that the generally higher abundant negative feedback species (superior competitors) decreased, the lower abundant positive feedback species (inferior competitors) increased, and vice versa (in ‘t Zandt et al, 2021). This balance may result from a dependency of the fast colonising, inferior competitors on the release of soil patches by slow colonising, superior competitors, akin to the proposed framework (Figure 5).…”
Section: Discussionsupporting
confidence: 88%
“…We selected plant species that naturally co‐occur in a species‐rich mountain meadow of which plant species abundances are stable on the large scale (community), but highly dynamic on the local scale (individuals) (Herben et al, 1995; Herben, Krahulec, Hadincová, & Kovářova, 1993; Herben, Krahulec, Hadincová, & Skálová, 1993). We previously showed that these fluctuations in abundance were linked to species‐specific soil conditioning effects (in ‘t Zandt et al, 2021). The selected species were grown in communities in an outdoor mesocosm facility in unconditioned soil with bare soil patches containing soil conditioned by one of four focal plant species, or a soil mixture of all four species as a non‐specific, control soil.…”
Section: Introductionmentioning
confidence: 95%
“…We propose that future PSF studies should strive for a higher level of resolution regarding which components of the soil communities influence plants and vice versa within PSF experiments. For starters, the field needs to thoroughly evaluate to what degree inoculation approaches are successful at establishing intended soil communities (Howard et al, 2017). Further, we propose that more groups of taxa need to be considered as drivers of PSF responses (e.g.…”
Section: Biological Resolution Considerationsmentioning
confidence: 99%
“…The great variation observed in how different species and genetic lineages vary in their feedbacks with soil biota has increasingly led researchers to question the role of phylogeny (e.g. in 't Zandt et al., 2021). These could arise if the pool of species used in the experiment share a certain degree of co‐evolution with pathogenic or mutualistic soil biota (Wandrag et al., 2020): closely related plant species often show morphological and chemical resemblance which may shape plant interactions with soil biota.…”
Section: Biological Resolution Perspectives On Plant‐soil Feedbacksmentioning
confidence: 99%
“…Chung et al ., 2019; in 't Zandt et al. , 2021), it should be possible to more properly place experimental results in a natural context to better predict how soil microbes influence plant community assembly.…”
Section: Discussionmentioning
confidence: 99%